The Metaphor of "War on Drugs" and "Mass Murder" in the Philippines: discourse analysis, power relations, and an interview with President Rodrigo Duterte - Brasilino, Gabriel Gama de Oliveira (Revista Neiba, Cadernos Argentina Brasil, 2019)
This article offers an analysis of statements pronounced by Rodrigo Duterte in an interview produced by Al Jazeera. It shows how Duterte tried to legitimize the extrajudicial killing of more than 3.500 citizens through these statements and rhetoric, a discourse dependent and effective through the metaphor of “war on drugs”, constructing drug dealers and users as threats, enemies to be “legitimately” killed. Drawing on Foucault's Discourse Analysis (1971), it argues that although war on drugs is a metaphor, and not war in the literal or modern sense, it is mobilized within a discursive strategy previous to, during, and after presidential elections; it is a juridical-political discourse on drugs and security that results in confrontations, hunting, punishment, and, in the limit, the exclusion or extermination of declared enemies. It also delineates the electoral context and the historical level of analysis, discussing the role of discourse analysis for critical security studies.